PERTUMBUHAN TUNAS ANGGREK DENDROBIUM SP. MENGGUNAKAN KOMBINASI BENZYL AMINO PURIN (BAP) DENGAN EKSTRAK BAHAN ORGANIKPADA MEDIA VACIN AND WENT (VW) - Tia Setiawati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
The purpose of this study was to get the best combination of BAP with organic material extract that can enhance the growth of Dendrobiumsp shoot in the VW media. The method used was experimental with completely randomized design, which consists of 12 treatments namely combination of BAP concentration with organic material extract. BAP concentration consisted of 4 levels i.e. 1 ppm, 2 ppm, 3 ppm and 4 ppm. The organic material extract used consisted of 3 types of extracts namely tomato extract, corn extract and banana extract, each of 100 mL/L. Each treatment was repeated 3 times. Data were analyzed using Analysis of Variance (Anova) and Duncan 's multiple range test. The results showed that the average of the fastest shoots emergence time obtained on combination of BAP 2 ppm + banana extract was 1.33 days after planting, the average of the highest shoot number was 14 buds obtained on the combination of BAP 3 ppm + tomato extract, and the average of the highest shoots length was 2.06 cm obtained on a combination of BAP 2 ppm + tomato extract. Keywords : BAP, Dendrobium sp., Extract, VW